(3eONd Gdi fXe GdeYdheGJ GdeMGSHjI (B/s - (3OjHGf, SjO YHO GdebUhOs; (3Gdajhej, eMeO eMeO hBNQhfs ((3GdEScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI(B, s, 2002)
(3EWGQ fXGe eYdheGJ GdeMGSHjI GdeGdjI(B- (3EWGQ fXGe GdeYdheGJ GdeMGSHjI GdEOGQjI(B- (3GdeMGSHI heaGgje GdfXe(B- (3COhGJ JMdjd hJUeje GdfXe(B- (3JMdjd GdJcdaI(B-(3GdefaYI aj JbSje GdfXe(B- (3GdfXe GdJWHjbjI dOhQGJ GdYedjGJ GdeMGSHjI(B- (3GdfXe GdEfSGfjI dJTZjd GdeYdheGJ(B- (3JUeje GdfXGe GdeMGSH GdeSJNOe ddMGSH(B- (3GdJYQja HbhGYO GdHjGfGJ(B- (3ESJNOGe bGYOI GdHjGfGJ dChd eQI(B- (3GdChGeQ GdeJbOeI dbGYOI GdHjGfGJ(B- (3HQeLI bhGYO GdHjGfGJ(B- (3JWHjb Ydi ESJNOGe GdMGSH aj GdeMGSHI GdeGdjI(B- (3Cef hhbGjI GdeYdheGJ aj Xd GdCfXeI GdeSJNOeI ddMGSHGJs
Keywords: (3GdeMGSHIs; (3GdeMGSHI GdEdcJQhfjIs; (3fXe GdeYdheGJ (B-(3GdeMGSHIs